Amperometric Biosensors for L-Arginine Determination Based on L-Arginine Oxidase and Peroxidase-Like Nanozymes - Nataliya Stasyuk; Galina Gayda; Olha Demkiv; Lyubomyr Darmohray; Mykhailo Gonchar; Marina Nisnevitch (Applied Sciences, 2021)
There are limited data on amperometric biosensors (ABSs) for L-arginine (Arg) determination based on oxidases that produce hydrogen peroxide (H2O2) as a byproduct of enzymatic reaction, and artificial peroxidases (POs) for decomposition of H2O2. The most frequently proposed Arg-sensitive oxidase-based ABSs contain at least two enzymes in the bioselective layer; this complicates the procedure and increases the cost of analysis. Therefore, the construction of a one-enzyme ABS for Arg analysis is a practical problem. In the current work, fabrication, and characterization of three ABS types for the direct measurement of Arg were proposed. L-arginine oxidase (ArgO) isolated from the mushroom Amanita phalloides was co-immobilized with PO-like nanozymes (NZs) on the surface of graphite electrodes. As PO mimetics, chemically synthesized NZs of CeCu (nCeCU) and NiPtPd (nNiPtPd), as well as green-synthesized hexacyanoferrate of copper (gCuHCF), were used. The novel ABSs exhibited high sensitivity and selectivity to Arg, broad linear ranges and good storage stabilities. Two ABSs were tested on real samples of products containing Arg, including the pharmaceutical preparation “Tivortine”, juices, and wine. A high correlation (R = 0.995) was demonstrated between the results of testing “Tivortine” and juice using nCeCU/GE and nNiPtPd/GE. It is worth mentioning that only a slight difference (less than 1%) was observed for “Tivortin” between the experimentally determined content of Arg and its value declared by the producer. The proposed ArgO-NZ-based ABSs may be promising for Arg analysis in different branches of science, medicine, and industry.